Defining the Genetic Features of O-Antigen Biosynthesis Gene Cluster and Performance of an O-Antigen Serotyping Scheme for Escherichia albertii - Wang, Hong; Zheng, Han; Li, Qun; Xu, Yanmei; Wang, Jianping; Du, Pengcheng; Li, Xinqiong; Liu, Xiang; Zhang, Ling; Zou, Nianli; Yan, Guodong; Zhang, Zhengdong; et al. (Frontiers in Microbiology, 2017)
Escherichia albertii is a newly described and emerging diarrheagenic pathogen responsible for outbreaks of gastroenteritis. Serotyping plays an important role in diagnosis and epidemiological studies for pathogens of public health importance. The diversity of O-antigen biosynthesis gene clusters (O-AGCs) provides the primary basis for serotyping. However, little is known about the distribution and diversity of O-AGCs of E. albertii strains. Here, we present a complete sequence set for the O-AGCs from 52 E. albertii strains and identified seven distinct O-AGCs. Six of these were also found in 15 genomes of E. albertii strains deposited in the public database. Possession of wzy/wzx genes in each O-AGC strongly suggest O-antigens of E. albertii were synthesized by the Wzx/Wzy-dependent pathway. Furthermore, we performed an O-antigen serotyping scheme for E. albertii based on specific antisera against seven O-antigens and a high throughput xTAG Luminex assay to simultaneously detect seven O-AGCs. Both methods accurately identified serotypes of 64 tested E. albertii strains. The E. albertii O1 serotype is not related to diarrheal patients, even though it is the dominant serotype. Our data revealed the highly genetic diversity of O-AGCs in E. albertii and indicated that horizontal gene transfer frequently occurred among the Enterobacteriaceae. We also provide valuable methods to reliably identify and serotype this bacterium.